Organization theory : critical and philosophical engagements - Peltonen, Tuomo (Emerald Group Publishing, 2016)
Understanding of the history and development of organization theory has recently made advances through work emerging on the history of management thought as well as through the institutionalization of critical approaches to organizations and organizational knowledge. This book provides a new reading of the historical development of organization.
Keywords: Organizational sociology.; elektronické knihy; electronic books